DAYA TERIMA DAN UJI PROKSIMAT SEREAL INSTAN SALVIZA DENGAN BAHAN DASAR BEKATUL, BIJI CHIA DAN TEPUNG KACANG HIJAU SEBAGAI MINUMAN ALTERNATIF PENANGGULANGAN OBESITAS REMAJA - Septiani, Alya Rahma; Susyani, Susyani; Telisa, Imelda (Poltekkes Kemenkes Palembang, 2022)
Background: Obesity is one of the diseases that experience an increase in prevalence every year. Diet arrangements low in energy and high in fiber can be done by obese people can carry out their diet. Goal : Make salviza instant cereal formula to be a good high fiber cereal drink for obese teens Method: This study is an experimental study using a non factorial RandomIzed Design (RAL) with 4 treatments. The study subjects were 25 organoleptic test panelists. Results : Based on the results of organoleptic test research (taste, texture, aroma and color) showed the preferred instant cereal salviza received is F3 with an average total receiving capacity of 16.56. The formula contains energy of 442.94 kcal (per 100 grams), protein 14.63%, fat 14.06%, carbohydrates 64.47%, water content of 3.83% and food fiber 9.84%. From the results of the analysis, the water content has not met the standards and fiber content of food is classified as high / rich. Conclusion : Based on the results of the study can be concluded that the addition of bran, chia seeds and green bean flour in instant cereals salviza can be used as an altefnative drink that is high in fiber to combat adolescent obesity. Keywords: Rice bran, chia seeds, green bean, organoleptic test, obesity